The Impact of Chronic Pelvic Pain and Bowel Morbidity on Quality of Life in Cervical Cancer Patients Treated With Radio (Chemo) Therapy. A Systematic Literature Review - Natuhwera G; Ellis P (Journal of Pain Research, 2025)
Germanus Natuhwera,1,2 Peter Ellis3 1Clinical and Administration Departments, Hospice Africa Uganda, Kampala, Uganda; 2Education Department, Institute of Hospice and Palliative Care in Africa, Kampala, Uganda; 3Canterbury Christ Church University, Canterbury, UKCorrespondence: Germanus Natuhwera, Email ngermans16@gmail.com; gnatuhwera@hospice-africa.orgAbstract: Introduction: Radiotherapy, administered with or without chemotherapy is the gold standard treatment for cervical cancer with both curative and palliative intent. However, the treatments often result in adverse events, mainly chronic pelvic pain and bowel morbidity, which can negatively impact quality of life.Aim: To systematically appraise peer reviewed evidence regarding chronic pelvic pain and bowel morbidity and their impact on quality-of-life of cervical cancer patients treated with radiotherapy with or without chemoradiation therapy.Design: A systematic review of original peer-reviewed research evidence.Data Collection Methods and Tools: A systematic search conducted between April and May 2021, and updated in September 2024, using PubMed, Hinari, CINAHL and Google Scholar, for peer reviewed papers published between 2008 and 2019. Data were extracted using a structured checklist designed to capture key elements about the methods and findings of the research.Results: There were 245 articles retrieved with 29 meeting the inclusion criteria. 11 studies were conducted in Europe, eight in Asia, one in North America, three in Africa, while six were multinational/multicontinental. 13 of the papers were longitudinal, 10 cross-sectional, three literature reviews, one open randomised controlled trial, and two retrospective studies of prospectively collected data. Studies reported disruptions in nearly all domains of quality-of-life, including global, physical, emotional/psychological, financial, sexual, social, role functioning as a result of being treated with radiotherapy or radio-chemotherapy.Conclusion: Chronic pelvic pain and bowel morbidity are common adverse events experienced by cervical cancer patients receiving, or who have received, pelvic radiotherapy or radio-chemotherapy. Symptoms occur to varying degrees and exert a negative toll on the quality-of-life of women. Clinicians should be more aware and prioritise thorough assessment and management of symptoms before, during and after treatment. There is limited population-based and longitudinal research about the topic, and on chronic pelvic pain in general, which limits generalisability. Longitudinal studies with more extended periods of follow-up are needed.Keywords: chronic pelvic pain, bowel morbidity, cervical cancer, quality of life, radio (chemo) therapy